Consultants and firm-level innovation performances: a doubly robust estimation approach - Odei, Samuel Amponsah; Odei, Michael Amponsah; Anderson, Henry Junior (Alexandru Ioan Cuza University of Iasi, 2020)
This paper examines firms use of external consultants and commercial labs as an essential source of knowledge for innovation performance and activities in the IT and other information service firms. Consultants are essential conduits to transfer knowledge, technologies and innovations to firms and other economic agents. Using data from the Eurostat Community Innovations Survey conducted between 2012 and 2014 and the doubly robust estimation methodology, this study, as expected, found a positive and statistically significant relationship between product and process innovations, intramural R&D, engagement in R&D, market introduction of innovations, engagement in other preparation influenced firms to rely on the services of external consultants. The results of the propensity-score matching also show that on average, firms that relied on the services of consultants were 61% more likely to improve their product innovations and 62% organizational innovations than those firms that didn't use them. The results are important for firm managers who are aiming to be innovative and can serve as a practical guide on how to improve firm-level innovation potentials and activities.
Konzultanti a inovační výkony na úrovni firmy: dvojnásobně robustní přístup k odhadu
Keywords: consultants; innovations; knowledge transfers; R&D; Czech Republic; konzultanti; inovace; transfer znalostí; V&V; Česká Republika